2005
DOI: 10.1088/0031-9155/50/18/003
|View full text |Cite
|
Sign up to set email alerts
|

Application of x-ray phase contrast imaging to microscopic identification of Chinese medicines

Abstract: In the last decade, x-ray phase contrast imaging (XPCI) has received considerable attention as a novel imaging technique, which has proved to be suitable for weakly absorbing materials such as biomedical samples and polymers. In this paper, the microstructures of traditional Chinese medicines (TCMs), which are used as judging criteria in the identification of TCMs, were investigated by XPCI based on a nano-focus x-ray tube. The results demonstrated that XPCI is a promising new method for the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The edge‐enhanced images produced by the PPCI approach are very useful, allowing for visualization of boundaries with different refraction properties. Wei et al successfully utilized PPCI to investigate the microstructures of traditional Chinese medicines . Moreover, the phase information contained in PPCI radiographic fringes could be extracted by means of phase‐retrieval, which enables the phase shift imposed on the wave by the sample to be recovered from the diffracted intensity distribution in the image plane or planes .…”
Section: Methodology Developmentmentioning
confidence: 99%
“…The edge‐enhanced images produced by the PPCI approach are very useful, allowing for visualization of boundaries with different refraction properties. Wei et al successfully utilized PPCI to investigate the microstructures of traditional Chinese medicines . Moreover, the phase information contained in PPCI radiographic fringes could be extracted by means of phase‐retrieval, which enables the phase shift imposed on the wave by the sample to be recovered from the diffracted intensity distribution in the image plane or planes .…”
Section: Methodology Developmentmentioning
confidence: 99%
“…To date, XPCMT has been used successfully for plant research [26], [27], [28]. X-ray phase-contrast microscopy has already provided preliminary exploratory results [29], [30], and XPCMT has been adapted to study CMM raw materials [3], [4]. In this study, XPCMT data processing using the phase-retrieval method was employed to obtain quantitative information about the microstructure of ginseng.…”
Section: Methodsmentioning
confidence: 99%
“…Since Röntgen discovered X-rays in 1895, X-ray imaging techniques have been applied in clinical diagnosis, industrial nondestructive inspections and many other areas. However, until 2005 [12], this technique was not employed in the field of the identification of CMMs. When an X-ray wave traverses an object, its amplitude and phase change, resulting in attenuation, interference, and refraction, and in X-ray phase-contrast imaging these are converted into intensity changes.…”
Section: Two-dimensional Characteristic Microstructures Of Cmmsmentioning
confidence: 99%
“…By using this laboratory X-ray imaging system described above, Wei et al began the microscopic identification of CMMs in 2004, even before the ground-breaking of the Shanghai Synchrotron Radiation Facility(SSRF) [12,40]. Some of the first research results are shown in figure 4.…”
Section: Two-dimensional Microstructures Imaged By X-ray Tube Based Xpcimentioning
confidence: 99%